Integrating Poster Comment Cooperative Learning with Longko’ Cultural Values to Enhance Students’ Learning Outcomes in Character Education - Erwin Bunga Sapan; Abdullah Pandang; Andi Makkasau; Syamsuddin Syamsuddin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving students' character education learning outcomes requires instructional models that are both interactive and culturally relevant. Traditional teaching methods often fail to fully engage students or reflect local cultural values. This study investigates the effectiveness of integrating the Poster Comment cooperative learning model with Longko’ cultural values to enhance students’ learning outcomes in character education. A 2×2 factorial experimental design was employed involving 100 undergraduate students from a Christian higher education institution in Indonesia. Participants were randomly assigned to four groups based on two variables: learning model (Poster Comment vs. Non-Poster Comment) and cultural integration (Longko’ vs. Non-Longko’). Learning outcomes were assessed through pre- and post-tests using validated multiple-choice and essay instruments. Data were analyzed using two-way ANOVA. The findings demonstrated significant main effects of both the learning model and cultural values on students' learning outcomes. The Poster Comment approach outperformed the Non-Poster model (?(1,46) = 45.77, p .001), and Longko’ cultural integration significantly improved scores compared to non-cultural approaches (?(1,46) = 196.40, p .001). A significant interaction effect (?(1,46) = 11.79, p = .001) indicated the greatest gains occurred when Poster Comment was combined with Longko’ values. Integrating cooperative learning with indigenous cultural values fosters deeper understanding and engagement, leading to improved learning outcomes in character education. This study highlights the importance of culturally responsive pedagogy in higher education and supports the development of localized, value-driven instructional models.